The so-called constitutional block as a parameter of constitutional interpretation, is it necessary in Peru? - Meza Hurtado, Artemio Daniel (2012)
The Constitutional Tribunal of the Peru, to fulfill the function of maximum interpreter of the Constitution, to determine the correct interpretation in a concrete case and to fulfill its main function, of determining the subjected unconstitutionality to its knowledge, does not only use the norms contained in the Constitution, it almost always goes to other norms and approaches that are known as the parameter of constitutionality or block of constitutionality whose necessity or importance is in debate